Ecofeminism Interpretations of Women’s Transformation in Indonesian Folktales - Citra Rizky Lestari; Agus Nuryatin; Mukh Doyin; Yusro Edy Nugroho (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study examines how Indonesian folktales present female characters transforming in response to social or cultural expectations. From an ecofeminist perspective, these narratives reflect deeper critiques of the intertwined marginalization of women and nature. Specifically, the study examines recurring motifs of female transformation into natural elements in three folktales: Nini dan Puteri Ikan, Asal Usul Kota Banyuwangi, and Legenda Ikan Patin. These stories portray women who, due to betrayal, grief, or societal pressure, undergo symbolic metamorphosis, particularly through transformations into fish or through symbolic fusion with water. The research employs a descriptive qualitative approach, applying thematic analysis with NVivo-style coding to identify patterns across texts. The analysis highlights three key themes: bodily transformation as a form of resistance or consequence, the weight of patriarchal expectations that restrict female agency, and spiritual or mystical symbolism that elevates the transformation beyond mere punishment. The findings suggest that these transformations function as both acts of protest and modes of renewal, expressing loss, liberation, and transcendence. Through this lens, the tales reveal cultural perspectives on women, morality, and human-nature relationships. Ultimately, the study contributes to gender and folklore scholarship by showing how narratives of female transformation encode socio-cultural anxieties and aspirations, offering alternative understandings of identity, power, and ecological interconnectedness.